Partnership strategy patterns of micro, small, and medium enterprises in increasing the productivity of crocodile leather artisans in Mimika Regency - Parrangan, Bertha; Iek, Mesak; Hafiziandra, Yundy (Goodwood Publishing, 2025)
Purpose: This study aims to analyze partnership strategies between Micro, Small, and Medium Enterprises (MSMEs) and various stakeholders particularly NGOs and financial institutions in enhancing the productivity of crocodile leather craftsmen in Mimika Regency, Papua. It explores how institutional collaboration can strengthen market access, financial literacy, and business sustainability. Research/Methodology: The study employs a qualitative descriptive approach using a case study design. Data were collected through in-depth interviews, observation, and documentation involving MSME actors, local government agencies, and partner institutions. Thematic analysis was conducted to identify emerging patterns and collaborative mechanisms. Results: The findings indicate that strategic partnerships, especially with NGOs and cooperative-based financial institutions, significantly enhance production management, marketing outreach, and product value among local craftsmen. NGOs play a vital role in mentoring, capacity building, and ensuring sustainability through continuous engagement. Nonetheless, the lack of formal contractual agreements and irregular raw material supply remain major constraints. Conclusions: Strategic partnerships with NGOs and financial institutions effectively improve productivity, capacity, and market access for crocodile leather MSMEs in Mimika. Yet, vulnerabilities within the supply chain—stemming from informal contracts and material instability—continue to pose risks. Strengthening institutional agreements and supply systems is crucial for achieving long-term MSME resilience. Limitations: The study focuses on a single regency and sector, limiting generalization. Contribution: This research enriches MSME development literature by highlighting the significance of sustained institutional partnerships and proposing a replicable hybrid collaboration model integrating financial inclusion and technical assistance.